Allocation of biomass and photoassimilates in juvenile plants of six Patagonian species in response to five water supply regimes - Cella Pizarro, Lucrecia (2010)
Background and Aims The growth-differentiation balance hypothesis (GDBH) states that there is a physiological trade-off between growth and secondary metabolism and predicts a parabolic effect of resource availability (such as water or nutrients) on secondary metabolite production. To test this hypothesis, the response of six Patagonian Monte species (Jarava speciosa, Grindelia chiloensis, Prosopis alpataco, Bougainvillea spinosa, Chuquiraga erinacea and Larrea divaricata) were investigated in terms of total biomass and resource allocation patterns in response to a water gradient. Methods One-month-old seedlings were subjected to five water supply regimes (expressed as percentage dry soil weight: 13%, 11%, 9%, 7% or 5%-field water capacity being 15%). After 150 d, plants were harvested, oven-dried and partitioned into root, stem and leaf. Allometric analysis was used to correct for size differences in dry matter partitioning. Determinations of total phenolics (TP), condensed tannins (CT), nitrogen (N) and total non-structural carbohydrates (TNC) concentrations were done on each fraction. Based on concentrations and biomass data, contents of TP and CT were estimated for whole plants, and graphical vector analysis was applied to interpret drought effect. Key ResultsFour species (J. speciosa, G. chiloensis, P. alpataco and B. spinosa) showed a decrease in total biomass in the 5% water supply regime. Differences in dry matter partitioning among treatments were mainly due to size variation. Concentrations of TP, CT, N and TNC varied little and the effect of drought on contents of TP and CT was not adequately predicted by the GDBH, except for G. chiloensis.Conclusions Water stress affected growth-related processes (i.e. reduced total biomass) rather than defence-related secondary metabolism or allocation to different organs in juvenile plants. Therefore, the results suggest that application of the GDBH to plants experiencing drought-stress should be done with caution, at least for Patagonian Monte species.